2021
DOI: 10.3390/ma14216377
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Numerical Comparison of Impact Behavior between Thermoplastic and Thermoset Composite for Wind Turbine Blades

Abstract: Damage generated due to low velocity impact in composite plates was evaluated focusing on the design and structural integrity of wind turbine blades. Impact properties of composite plates manufactured with thermoplastic and thermoset resins for different energy levels were measured and compared. Specimens were fabricated using VARTM (vacuum assisted resin transfer molding), using both matrix systems in conjunction with carbon, glass and carbon/glass hybrid fibers in the NCF (non-crimp fabric) architecture. Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 68 publications
0
4
0
Order By: Relevance
“…Wind turbine blades are made of composite materials as well as sandwich sections (Fig. 2) that are weak in through the thickness direction, thus impact loads on blades can be detrimental to their structural integrity [8,25]. In addition, complex failure modes are obtained under impact loads that simultaneously interact and are sometimes visually undetectable [26].…”
Section: Nomenclaturementioning
confidence: 99%
“…Wind turbine blades are made of composite materials as well as sandwich sections (Fig. 2) that are weak in through the thickness direction, thus impact loads on blades can be detrimental to their structural integrity [8,25]. In addition, complex failure modes are obtained under impact loads that simultaneously interact and are sometimes visually undetectable [26].…”
Section: Nomenclaturementioning
confidence: 99%
“…For instance, Pinto et al reported that glass/carbon fiber reinforced composites (FRCs) produced with elium and epoxy resin exhibit similar behavior for using the same fiber reinforcement; also, composites with elium matrix had shown less impact damage. 9 Bhudolia et al measured 16.3% higher impact load bearing for carbon/elium composite pipes than epoxy counterparts. Bending test results also revealed that both composite groups have comparable load-bearing capacity, and the elium matrix exhibits less delamination damage.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, significant attempts have been noted in the literature scrutinizing the mechanical attributes of this novel elium resin‐based composites consisting of different fiber reinforcements. For instance, Pinto et al reported that glass/carbon fiber reinforced composites (FRCs) produced with elium and epoxy resin exhibit similar behavior for using the same fiber reinforcement; also, composites with elium matrix had shown less impact damage 9 . Bhudolia et al measured 16.3% higher impact load bearing for carbon/elium composite pipes than epoxy counterparts.…”
Section: Introductionmentioning
confidence: 99%
“…However, the material properties of the thermoplastic-based composite are not readily available as in the case of the Epoxy-based composite. Although, some researchers [ 14 ] have determined the impact behavior of the thermoplastic-based composite for wind turbine blade application. However, no research has been conduct like this or keep it aed on determining the thermoplastic composite’s tensile strength and tensile modulus, which are crucial factors in designing the hydrogen tank.…”
Section: Introductionmentioning
confidence: 99%